Use of TiO2 Powder and Activated Carbon as Catalytic Ceramic Filling Material to Reduce Hazardous Pollutants on Gasoline Engine - Setiyono, Dwi Rahmad; Widjanarko, Dwi (Jurnal Rekayasa Kimia & Lingkungan, 2018)
The purpose of this study was, 1) to examine the effect of the mixture composition between ceramics, TiO2, and activated carbon on catalytic converters on vehicle exhaust emissions, 2) test the composition of the mixture between ceramic, TiO2, and activated carbon in catalytic converters that produce the most exhaust emissions low. This study uses an experimental method with descriptive statistics. The independent variable is catalytic converter with a variety of ceramic material composition with a mixture of TiO2 and activated carbon. Control variables are the composition of the mixture, catalytic converter porosity control, standard exhaust without catalytic converter, engine speed used at stationary speed, and duration of testing time. Dependent variables are vehicle exhaust emissions CO and HC. The results of this study are, 1) The use of ceramic materials mixed with TiO2 and activated carbon in catalytic converters can reduce CO and HC content in gasoline-powered vehicles. 2) The best reduction is in the composition of 50% ceramic material, 25% TiO2, and 25% activated carbon, which is able to reduce CO content from 4.19% to 1.44% and HC gas. Suggestions from this study are, gasoline-powered vehicles can use catalytic converters made from Ceramic with a mixture of TiO2, and activated carbon with a composition of 50% ceramic material, 25% TiO2, and 25% activated carbon.